A Survey of Kiswahili Literature: 1970-1988 - Mulokozi, Mugyabuso M. (Afrika Focus, 1992)
A survey is given of the development of Kiswahili written literature during the past two decades. Particular attention is given to (a) the rise of the socially critical literature, (b) the emergence of experimental forms of literature, (c) the growing popularity of pop’fiction, (d) the continued development of the nationalistic-cum- cultural novel and (e) the quantitative and qualitative growth of Kiswahili translations. All this is placed against the background of East-African cultural and political developments since Independence. KEY WORDS: Tanzania, Swahili, literature (poetry, drama, fiction), East African historical and political development